2007
DOI: 10.5009/gnl.2007.1.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Levels in Gastric Mucosa before and after Eradication of Helicobacter pylori

Abstract: These results show that H. pylori infection has no effect on stomach ghrelin levels and that eradication therapy does not influence plasma or tissue ghrelin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…It has been demonstrated that central ghrelin administration inhibits gastric acid secretion, but that peripheral ghrelin administration does not modify gastric acid secretion in rats. Thus, the possibility exists that ghrelin and H. pylori infection may be associated (Choe et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that central ghrelin administration inhibits gastric acid secretion, but that peripheral ghrelin administration does not modify gastric acid secretion in rats. Thus, the possibility exists that ghrelin and H. pylori infection may be associated (Choe et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its intimate relationship with the gastric epithelium, H . pylori , the dominant member of the gastric microbiota, has the potential to affect the regulation of normal energy homeostasis of humans [ 8 10 , 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma and gastric mucosal ghrelin levels after H. pylori eradication were also shown by Deng et al [103] in 50 children with H. pylori-associated functional dyspepsia. However, a study reported by Choe et al [109] failed to show a relationship between H. pylori infection and stomach mucosal ghrelin levels, with no effect of eradication therapy. It should be noted that a greater BMI and corpus predominant gastritis are recognized as independent risk factors for eradication failure [110] .…”
Section: Weight Controlmentioning
confidence: 95%